Which Praise of Folly Did the Spanish Censors Read? - Ledo, Jorge (Erasmus Studies (2451-9723), 2018)
The discovery and subsequent edition of the only known sixteenth-century Spanish translation of The Praise of Folly (which should now be dated ca. 1532-1535) put into question the notion that Erasmus was almost exclusively received as a doctrinal author in sixteenth-century Spain. To bolster this argument, these pages examine the 1536 Spanish translation of Alberto Pio's Tres et viginti libri locos lucubrationum variarum D. Erasmi Roterodami. Though this translation was not unknown to scholars, none realized that book iv, part 1 included a partial translation, paraphrase, and commentary of the Praise of Folly. Once recognized, this translation allows us more accurately to date the Moria de Erasmo and in turn demands an explanation of why Pio's lengthy text was translated into Spanish. Moreover, this material helps to explain what texts the Spanish censors had in mind when referring to the "Moria of Erasmus in romance, Latin, and any other language.